Pengaruh Budaya Perusahaan Terhadap Kinerja Karyawan (Studi Kasus Ponpes Mukmin Mandiri Sidoarjo) - habibie, muhammad; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2021)
Corporate culture is the value of a role that can be trusted and is embedded in the company's activities, which can be realized on an ongoing basis by the behavior of employees to achieve company goals. This study aims to analyze the influence of corporate culture and work environment simultaneously on employee performance. This research uses quantitative research. The research sample was taken using a purposive sampling technique with a total sample of 350 students. Collecting data by giving questionnaires to students who work in the Mukmin Mandiri Islamic Boarding School Sidoarjo. Data analysis using validity, reliability, coefficient of determination test (R2) has the effect of corporate culture on employee performance variables is 50.8%. and also on the partial regression coefficient test (t test) with the calculation of the variable X with Y. If the value of the company has increased by 1%, then employee performance will increase by 88%, other assumptions of the independent variable are constant. The results of the study obtained a positive relationship between the corporate culture variable and the employee performance variable being the dependent variable. The next research is expected to update the quality of employees in their performance..